REHABILITASI MEDIK PADA PENDERITA DISFAGIA - Pandaleke, Jenny J. C.; Sengkey, Lidwina S.; Angliadi, Engeline (Jurnal Biomedik : JBM, 2014)
Abstract: Dysphagia is a common symptom in clinical pratice, suffered by all age groups, and associated with multiple systemic disorders, inter alia: diabetes mellitus, hyperthyroidism, lupus erythematosus, dermatomyositis, stroke, as well as Parkinson’s and Alzheimer’s diseases. The diagnosis of dysphagia is based on anamnesis, physical examination (including examination of the patient during eating or drinking), and supporting examination, such as videofluorographic swallowing study (VFSS) and fiberoptic endoscopic evaluation of swallowing (FEES). The management of dysphagia in the medical rehabilitation field requires a teamwork consisting of a physical therapist, a speech therapist, an occupational therapist, rehabilitation nurses, as well as a nutritionist and several other specialists. The occurence of dysphagia is closely connected with malnutrition, dehydration, respiratory tract infections, duration of hospitalization, and even death. Therefore, early diagnosis and treatment are very important in the management of dysphagia.Keywords: dysphagia, rehabilitationAbstrak: Disfagia sering ditemukan dalam praktek klinik, dan bisa diderita oleh semua kelompok usia dan berhubungan dengan multiple systemic disorders, antara lain diabetes melitus, hipertiroidisme, lupus eritematosus, dermatomiositis, stroke, serta penyakit Parkinson dan Alzheimer. Diagnosis disfagia ditegakkan melalui anamnesis, pemeriksaan fisik (termasuk pemeriksaan saat penderita makan atau minum), dan pemeriksaan penunjang seperti videofluroskopi dan fiberoptic endoscopic evaluation of swallowing (FEES). Penanganan dalam bidang rehabilitasi medik membutuhkan kerjasama tim yang terdiri dari seorang dokter spesialis kedokteran fisik dan rehabilitasi, ahli terapi bicara, ahli terapi okupasi, perawat rehabilitasi, dan juga membutuhkan kerjasama dengan seorang ahli gizi dan beberapa bidang spesialisasi yang lain. Disfagia sangat berhubungan dengan terjadinya malnutrisi, infeksi saluran pernapasan, dehidrasi, bertambahnya jumlah hari rawat, dan bahkan kematian. Oleh karena itu, diagnosis dan penanganan dini sangat dibutuhkan dalam penatalaksanaan disfagia.Kata kunci: disfagia, rehabilitasi